Leadership-as-Practice: Its Past History, Present Emergence, and Future Potential - Joseph A. Raelin (Academy of Management Collections, 2023)
In this essay the author through a curation of articles drawn largely from the archives of the Academy of Management guides readers through the early foundations, principles, and theory of the new field of leadership-as-practice or L-A-P. The field is shown to have evolved through a history of leadership research culminating in a plural tradition with which the practice perspective is allied. Some of the critical issues in the present and unfolding state of L-A-P are exemplified along with their implications for ongoing leadership practice. The essay ends with some recommendations for future research in the field along with the opportunities for advancing theory and application that such study might afford.
Keywords: J24; M10; M12; M14; M53; M54; 330; leadership-as-practice; practice theory; collective leadership; pragmatism; agency; leadership development; collective identity; reflexivity; dialogue